Asas-asas Teknik Kaunseling Dakwah - Mohd Zin, Ab. Aziz; Md. Yusoff, Yusmini (Jurnal Usuluddin, 2001)
The article will briefly discuss the techniques of counseling da'wah based on a number of Hadiths and Qur'anic. Although not all counseling techniques can be generalized with the verses, there are evidences that show fundamental techniques of counseling da'wah are similar to the techniques in conventional counseling.